2007
DOI: 10.1159/000100781
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Obesity Does Not Appear to Be Increased after Treatment of Acute Lymphoblastic Leukemia in Brazilian Children: Role of Leptin, Insulin, and IGF-1

Abstract: Background/Aims: It has been reported that children treated for acute lymphoblastic leukemia (ALL) in developed countries show an increased risk of overweight and obesity in adolescence and adulthood. However, the majority of patients who came to our observation in Brazil have low or normal body weight and only one of them was obese. Therefore, we have decided to assess some biochemical parameters possibly related to the intermediate metabolism and body composition in these patients. Methods: Two groups of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 101 publications
2
23
0
Order By: Relevance
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies 8,29,33,38 reported separate BMI z scores for survivors treated with and without CRT, 3 studies 34,35,39 included exclusively survivors treated with CRT, and 7 studies 12,13,24,26,27,32,37 included exclusively survivors treated without CRT. On the basis of these 14 studies, the BMI z score for the 478 survivors treated with CRT was 0.9 (95% CI: 0.5-1.3), and the BMI z score for the 830 survivors treated without CRT was 0.7 (95% CI: 0.4-0.9; Fig 3).…”
Section: Obesity In Pediatric All Survivors By Patient and Treatment mentioning
confidence: 99%
“…Insulin is also involved in the pathophysiology of obesity following lesions to the hypothalamus-pituitary region (41). It has been suggested that obese patients with insulin resistance have a diminished sensitivity to insulin action in the hypothalamus-pituitary-gonadal axis due to the production of cytokines and hormones by the adipose tissue (29).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other authors have found no correlation between insulin sensitivity and basal, GnRH-or clomiphene-stimulated LH secretion (29,30). Nevertheless, the concentrations and pulse amplitude of LH may be abnormal in morbid obesity patients (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…CRT received at a young age may blunt hypothalamic leptin sensitivity and thereby alter the body's response to leptin and the regulation of body weight, metabolism, and reproductive function [3]. Two recent studies have reported about significantly higher leptin levels in survivors of ALL treated by CRT [4,5]. Hence, there may be a possibility of radiation-induced hypothalamic resistance to leptin.…”
Section: Introductionmentioning
confidence: 99%